Implementasi Personalized Learning Berbasis Kecerdasan Buatan (AI) terhadap Peningkatan Kompetensi Literasi dan Numerasi Siswa Sekolah Dasar Negeri Terrak 1 Pamekasan - Arifin, Samsul; Kamila Novita, Tsurayya (AL -ALLAM, 2025)
This study aims to describe the implementation of Artificial Intelligence (AI)-based personalized learning to enhance the literacy and numeracy competencies of students at SDN Terrak 1 Pamekasan. Facing the challenges of diverse student abilities and the limitations of the classical teaching approach, AI offers a solution through an adaptive learning platform. This research employed a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews, focus group discussions (FGD), and document analysis. The findings indicate that the AI platform significantly increases student motivation, marked by a shift from extrinsic motivation driven by gamification to intrinsic motivation stemming from a sense of mastery. The system successfully personalizes learning paths with precision according to each student's Zone of Proximal Development (ZPD). Consequently, the teacher's role transforms from an information deliverer to a data-informed facilitator who provides targeted interventions. Nevertheless, the implementation faces challenges such as technical infrastructure constraints, initial teacher resistance, and the potential for a digital divide. In conclusion, the success of AI-based personalized learning depends not only on the technology's sophistication but also on the overall readiness of the educational ecosystem, particularly sustainable teacher professional development and equitable policies.